Cost-effectiveness of catheter-based radiofrequency renal denervation for the treatment of uncontrolled hypertension: an analysis for the UK based on recent clinical evidence - Sharp, Andrew S.P.; Cao, Khoa N.; Esler, Murray D.; Kandzari, David E.; Lobo, Melvin D.; Schmieder, Roland; Pietzsch, Jan B. (European Heart Journal - Quality of Care and Clinical Outcomes, 2024)
Aims Catheter-based radiofrequency renal denervation (RF RDN) has recently been approved for clinical use in the European Society of Hypertension guidelines and by the US Food and Drug Administration. This study evaluated the lifetime cost-effectiveness of RF RDN using contemporary evidence. ............................................................................................................................................................................................ Methods and A decision–analytic model based on multivariate risk equations projected clinical events, quality-adjusted life years results (QALYs), and costs. The model consisted of seven health states: hypertension alone, myocardial infarction (MI), other symptomatic coronary artery disease, stroke, heart failure (HF), end-stage renal disease, and death. Risk reduction associated with changes in office systolic blood pressure (oSBP) was estimated based on a published meta-regression of hypertension trials. The base case effect size of −4.9 mmHg oSBP (observed vs. sham control) was taken from the SPYRAL HTN-ON MED trial of 337 patients. Costs were based on National Health Service England data. The incremental cost-effectiveness ratio (ICER) was evaluated against the UK National Institute for Health and Care Excellence (NICE) cost-effectiveness threshold of £20 000–30 000 per QALY gained. Extensive scenario and sensitivity analyses were conducted, including the ON-MED subgroup on three medications and pooled effect sizes. RF RDN resulted in a relative risk reduction in clinical events over 10 years (0.80 for stroke, 0.88 for MI, 0.72 for HF), with an increase in health benefit over a patient’s lifetime, adding 0.35 QALYs at a cost of £4763, giving an ICER of £13 482 per QALY gained. Findings were robust across tested scenarios. ............................................................................................................................................................................................ Conclusion Catheter-based radiofrequency RDN can be a cost-effective strategy for uncontrolled hypertension in the UK, with an ICER substantially below the NICE cost-effectiveness threshold.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Cost–benefit analysis; Denervation; England; Hypertension; Radio frequency ablation